Comportamientos en la prevención de riesgos laborales en trabajadores de construcción civil del Consorcio Bellavista LC. 2023 - López Flores, Gresia Sthefanny (2024)
Bellavista LC Consortium's diverse workforce in 2023, with an experienced core aged 35 to 54, highlights key challenges. The marked gender disparity underscores the urgent need for inclusive strategies in civil construction. The variability in educational levels indicates the importance of adapting security strategies. Although the stability derived from work experience is positive, there may be resistance to change. Divergent perceptions about the relationship between experience and accidents highlight the importance of addressing long-held beliefs. Although there is awareness of risks in new tasks, the lack of correlation with training suggests the need to evaluate the effectiveness of the programs. Variability in the use of personal protective equipment (PPE) points to the need for greater consistency. Despite positive attitudes toward supervision, perceived pressure and lack of reporting of unsafe conditions need exploration. The correlation between experience and accidents indicates the need to address attitudes of overconfidence. Together, these findings highlight the importance of specific interventions to strengthen the safety culture and reduce workplace accidents at the Bellavista LC Consortium.